On the structural stability of astrophysical jets - Vlahakis, N.; Tsinganos, K. (Joint European and National Astronomical Meeting, 1997)
General theorems and various analytical self-similar solutions have recently shown that magnetized and rotating astrophysical outflows may become asymptotically cylindrical, in agreement with observations of cosmical jets. A notable common feature in all such self-consistent, self-similar MHD solutions is that before final cylindrical collimation is achieved, the jet passes from a stage of oscillations in its radius, Mach number and other physical parameters. It is shown that under rather general assumptions this oscillatory behavior of collimated outflows is not restricted to the few specific models examined so far, but instead it seems to be a rather general physical property of an MHD outflow which starts noncylindrically before it reaches collimation. It is concluded thence that astrophysical jets are structurally stable to small amplitude, time-independent perturbations in their asymptotically cylindrical shape.